Bridging Job Aspirations, Attitudes, and Educational Attainment in Mathematics Teaching and Learning: A Systematic Literature Review - G.C., Laxmi; Dahal, Prem Prasad; Pokhrel, Maheshor (GS Spark: Journal of Applied Academic Discourse, 2025)
This systematic literature review explores how job aspirations, attitudes toward education, and socio-cultural factors influence educational attainment in mathematics. Drawing on peer reviewed studies and theoretical frameworks, including Bourdieu’s cultural capital theory, sub cultural theory, and Marxist perspectives on class inequality, the review synthesizes findings to understand how social class mediates access to educational resources and shapes students’ academic outcomes in mathematics. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, systematically the study analyzed 10 peer-reviewed articles published between 2000 and 2023. The findings reveal that middle-class students benefit from greater cultural capital, parental involvement, and supportive attitudes toward long-term educational goals, while working class students face structural barriers such as material deprivation, limited exposure to academic language, and fewer opportunities for enrichment. The review concludes with practical and policy recommendations, including the integration of career guidance into mathematics instruction, culturally responsive pedagogy, and equitable resource distribution to address systemic inequities in mathematics education.